2008
DOI: 10.1128/mcb.00256-08
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles for NFAT Transcription Factor Genes as Oncogenes and Tumor Suppressors

Abstract: Nuclear factor of activated T cells (NFAT) was first described as an activation and differentiation transcription factor in lymphocytes. Several in vitro studies suggest that NFAT family members are redundant proteins. However, analysis of mice deficient for NFAT proteins suggested different roles for the NFAT family of transcription factors in the regulation of cell proliferation and apoptosis. NFAT may also regulate several cell cycle and survival factors influencing tumor growth and survival. Here, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
162
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 45 publications
7
162
2
Order By: Relevance
“…35 Along the same lines, NFAT1 activation or overexpression has been demonstrated to induce cell cycle arrest or cell death in T lymphocytes, Burkitt's lymphoma, and NIH 3T3 fibroblasts. [44][45][46] However, the molecular mechanisms by which NFAT1 induces cell cycle arrest in these cell types remain unknown. Together, our results support the notion that NFAT1 transcription factor works as a cell cycle repressor during the G1/S phase transition in B lymphocytes, and may contribute to controlling the tumorigenesis process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Along the same lines, NFAT1 activation or overexpression has been demonstrated to induce cell cycle arrest or cell death in T lymphocytes, Burkitt's lymphoma, and NIH 3T3 fibroblasts. [44][45][46] However, the molecular mechanisms by which NFAT1 induces cell cycle arrest in these cell types remain unknown. Together, our results support the notion that NFAT1 transcription factor works as a cell cycle repressor during the G1/S phase transition in B lymphocytes, and may contribute to controlling the tumorigenesis process.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of NFAT1 in other systems, it has been shown that lack of NFAT1 induces neoplastic transformation of cartilage cells and increased susceptibility to chemically-induced sarcoma formation in mouse models. 46,59 Also, constitutively active NFAT1 (CA-NFAT1) was able to antagonize H-RasV12 oncogene-induced transformation of NIH 3T3 fibroblasts. 46 Collectively, these data suggest a tumor suppressor role for NFAT1 in different cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that constitutively active forms of NFATc1 and NFATc2 induce two distinct phenotypes in NIH 3T3 cells; whereas NFATc1 increases their proliferation capacity and transformation (34,35), NFATc2 causes their cell cycle arrest and apoptosis (35). NFATc1 has also been shown to mediate VEGF-induced endothelial cell proliferation (36).…”
Section: Discussionmentioning
confidence: 99%
“…While both NFATc3 and c4 are permanently localized in the nuclei, an increase in intracellular Ca ++ level results in the nuclear translocation of both NFATc1 and c2 and specifies them as putative targets of activation signals in macrophages [23]. Due to the two alternative promoters P1 and P2, two poly A addition sites and alternative splicing events the Nfatc1 gene is expressed in numerous cell types as six alternative protein isoforms, which differ in their proliferative and apoptotic activities [24,25]. Similar to NFATc2 which supports anergy and suppresses proliferation [3], the P2-directed NFATc1β isoforms exert antiproliferative activities while the P1-directed α-isoforms support the proliferation and survival of lymphocytes.…”
Section: Introductionmentioning
confidence: 99%